Mengupas Stereotipe Mistis Ritual Seblang Olehsari dalam Ruang Virtual - Reefadhinta Novta A.; Rifdah Nurjihan S.; Rica Agatha (Institut Nalanda, 2023)
The mystical stereotyped of Seblang ritual with an innacurate understanding spreads informations presented in the mass media. Some of people’s comprehension not entirely true because virtual space triggers people to realize that Seblang is a hideous ritual. Informations spread in the mass media make the reader not really understand with the intention of information provider. The comprehension of Seblang ritual as a hideous ritual will continue build people’s meaning construction especially in virtual space. Presentation of this paper researcher uses qualitative research with an ethnographic approach to explore stereotypes that spreads in virtual space regarding hideous mystical perspectives using simulacra theory.